Normoxemic hypoxia of toxicological etiology and its current management as a cause of sudden and collective cyanosis: A propósito de un caso (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2024)
Cellular or mitochondrial respiratory failure is a poorly defined entity in emergency services; there are no protocols to address it and its failure to identify it early can lead to negative results. Its diagnosis is made when other pathologies are ruled out as a cause of pulmonary respiratory failure and due to high lactate values in blood gas analysis with normal gases. The main cause of tissue hypoxia is hypoxemic and anemic etiology, followed by shock states and finally histotoxic etiology. In this clinical case, its relevance due to poisoning by methemoglobinizing substances in a family led to alerting the ease of accidental poisoning by this type of substances available in compounds for daily use. I also frame the usefulness of elementary diagnostic tools such as clinical history and medical reasoning, directed towards a timely diagnosis and treatment of this type of acute respiratory failure with cyanosis not responsive to oxygen therapy of non-cardiopulmonary etiology that required on this occasion only conservative management.
Keywords: Hypoxia; mitochondrial respiration; methemoglobinemia; cellular respiratory failure